If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + 2(5p + -3) + -8p = 26 Reorder the terms: 6p + 2(-3 + 5p) + -8p = 26 6p + (-3 * 2 + 5p * 2) + -8p = 26 6p + (-6 + 10p) + -8p = 26 Reorder the terms: -6 + 6p + 10p + -8p = 26 Combine like terms: 6p + 10p = 16p -6 + 16p + -8p = 26 Combine like terms: 16p + -8p = 8p -6 + 8p = 26 Solving -6 + 8p = 26 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 8p = 26 + 6 Combine like terms: -6 + 6 = 0 0 + 8p = 26 + 6 8p = 26 + 6 Combine like terms: 26 + 6 = 32 8p = 32 Divide each side by '8'. p = 4 Simplifying p = 4
| 4.25=v^2/2850 | | z+12=-5 | | 4y^2-8y-60=0 | | -78+6x=122-4x | | 4.7x-5=3.7x+5 | | 3y+2y+4y+9x= | | Y^2-10y-16=0 | | 13+2(m-4)=-9 | | x^2-20x+100=32 | | 3(2b+1)=9 | | 1x+83=92 | | -38-9x=22-4x | | 0.70x+.05(10-x)=.10(-112) | | 9(2w-1)=27 | | 19.1213+19.28-3.496z-49.2-7.33z= | | (4a-7)(3a-8)=0 | | 15/45=x/3 | | 3(5x-1)-14x=3 | | -3x-105=-10x+49 | | f(8)=12 | | 3=-2x+9 | | 5/9d+83=4/9d+92 | | 4x-3(7-x)+2= | | -1.6x^2-3.2x=-18 | | 14-4x=2x+2 | | (15x^4+16x^3-8x)(3x^5+4)= | | X^2-X+XY-Y=0 | | 7(n+2)=-7 | | (-3x+4)+(4x-2)= | | -105-x=7x+47 | | 2b+10=8b-14 | | 3(x+3)-9= |